Media coverage of violence against women in the family and in an intimate partner relationship in Serbia - Resimić Miloš (Temida, 2016)
This article examines the media coverage of violence against women in the family and in an intimate partner relationship in Serbia. The goal of this article is to point to the potential that implementing the relevant state policies might have on the quality of the media coverage, by analysing the effects of state policies on the media coverage of violence against women in the family and in an intimate partner relationship. This study utilizes quantitative content analysis and qualitative framing analysis on a sample of 330 articles of Serbian daily newspapers Blic, Kurir and Politika in two time periods (three months in 2006 and three months in 2013). The results of the quantitative content analysis show a significant increase in the number of articles containing information on statistics, services for victims and expert sources. Qualitative framing analysis points to the conclusion that the nature of the media frame has not meaningfully changed. Namely, under the pressure of editors, journalists continue with framing violence against women in a stereotyped fashion which reflects the suppressed position of women in the Serbian society.